Polymersome-to-coacervate transformations. (September 2017) - Nakai, Keita; Kwolek, Urszula; Bednar, Jan; Zatorska, Maria; Nowakowska, Maria; Kepczynski, Mariusz; Yusa, Shin-ichi
Graphical abstract: Highlights: Two oppositely charged zwitterionic-ionic diblock copolymers can form nanovesicles. The nanovesicles can be transformed into coacervates by changing ionic strength. Polymersome-to-coacervate transformation is reversible. Abstract: Polymersomes and complex coacervates have been the subject of considerable interest due to their wide application as compartments for the encapsulation of various actives. In this paper, we present for the first time that the transformation of small unilamellar vesicles (polymersomes) to coacervate microdroplets is possible by a simple adjustment of the ionic strength. We demonstrated that a pair of zwitterionic-ionic copolymers self-assembles in an aqueous medium forming small unilamellar polymersomes. Cryo-transmission electron microscopy showed that the polymersomes had a diameter of 120 ± 49 nm and a membrane thickness of 25–30 nm. The polymersomes are stable at low ionic strength including physiological conditions, but they can be transformed into the coacervate microdroplets of several µm in diameter by increasing the salt concentration. The process can be reversed by reducing the salt concentration, what leads to the spontaneous formation of giant or small polymersomes. These studies contribute to the development of polymeric materials that can self-organize into ionic strength- responsive vesicular and solid structures (without the use of organic solvents) potentially useful for compartmentalization.